2010
DOI: 10.5047/eps.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of maximum earthquake magnitudes in future time intervals: application to the seismicity of Japan (1923–2007)

Abstract: We have modified the new method for the statistical estimation of the tail distribution of earthquake seismic moments introduced by Pisarenko et al. (2009) and applied it to the earthquake catalog of Japan . The newly modified method is based on the two main limit theorems of the theory of extreme values and on the derived duality between the generalized Pareto distribution (GPD) and the generalized extreme value distribution (GEV). Using this method, we obtain the distribution of maximum earthquake magnitudes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
0
11
0
1
Order By: Relevance
“…The distribution function generalized extreme value is defined as follows (Pisarenko, 2007(Pisarenko, , 2008(Pisarenko, , 2010:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution function generalized extreme value is defined as follows (Pisarenko, 2007(Pisarenko, , 2008(Pisarenko, , 2010:…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of the Generalized Extreme Value Distribution (GEV) can solve this problem. This probabilistic method has been developed by Pisarenko and his colleagues to evaluate the maximum earthquake magnitude for many catalogs such as the Harvard earthquake list (Pisarenko et al, 2008(Pisarenko et al, , 2014, the Japanese earthquake catalog (Pisarenko et al, 2010),… Thus, in general, it has been shown that the East Sea area has the potentially high seismic risk. However, historical earthquake data and machine data were used and the magnitudes have not been unified.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to use a magnitude-frequency distribution with no a priori prescribed analytical shape (e.g., Kijko, 2004). Other methods use the theory of extreme values of random variables (Pisarenko et al, 2008(Pisarenko et al, , 2010. These various methods are based only on the observed seismicity data.…”
Section: Usual Methodsmentioning
confidence: 99%
“…Previous estimates for M max varied from 9 (McCaffrey, 2008, using scaling relations and fault segment lengths) to 10 (if confidence limits are high) (Zöller et al, 2014, using the tapered GR distribution, but not conservation of moment). Using the theory of extreme values, Pisarenko et al (2010) found the absolute M max to be 9:57 0:86 for Japan. With the model and assumptions here, there is a 30% chance that M w ≤ 9 could be M max , but almost zero chance that it would be as large as M w 10.…”
Section: Japan Trenchmentioning
confidence: 99%
“…In the study of earthquakes, the EVT is a relevant tool, providing important information, such as the estimation of the probability of occurring a large earthquake over a long period of time or high quantiles (see e.g. Pisarenko et al (2010)). …”
Section: Introductionmentioning
confidence: 99%